Drug-Eluting Balloon versus New-Generation Drug-Eluting Stent for the Treatment of In-Stent Restenosis: An Updated Systematic Review and Meta-Analysis - Cui, Kong-Yong (Chin Med J (Engl), 2018)
BACKGROUND: Currently, drug-eluting balloon (DEB) appears to be an attractive alternative option for the treatment of in-stent restenosis (ISR). Nevertheless, the clinical outcomes of DEB have seldom been compared to those of new-generation drug-eluting stent (DES). Thus, this meta-analysis aimed to evaluate the safety and efficacy of DEB compared to those of new-generation DES in the treatment of ISR. METHODS: A comprehensive search of electronic databases including PubMed, EMBASE, and Cochrane Library up to November 2, 2017 was performed to identify pertinent articles comparing DEB to new-generation DES for the treatment of ISR. In addition, conference proceedings for the scientific sessions of the American College of Cardiology, American Heart Association, European Society of Cardiology, Transcatheter Cardiovascular Therapeutics, and EuroPCR were also searched. The primary endpoint was target lesion revascularization (TLR) at the longest follow-up. Dichotomous variables were presented as risk ratios (RR s) with 95% confidence intervals (CIs), while the overall RRs were estimated using the Mantel-Haenszel random-effects model. RESULTS: Five randomized controlled trials (RCTs) and eight observational studies involving 2743 patients were included in the present meta-analysis. Overall, DEB was comparable to new-generation DES in terms of TLR (RR = 1.24, 95% CI: 0.89–1.72, P = 0.21), cardiac death (RR = 1.55, 95% CI: 0.89–2.71, P = 0.12), major adverse cardiovascular event (RR = 1.21, 95% CI: 0.98–1.48, P = 0.07), myocardial infarction (RR = 1.12, 95% CI: 0.72–1.76, P = 0.62), and stent thrombosis (RR = 0.95, 95% CI: 0.38–2.42, P = 0.92). However, DEB was associated with higher risk of all-cause mortality than new-generation DES (RR = 1.65, 95% CI: 1.09–2.50, P = 0.02). This was especially true in the real-world observational studies (RR = 1.79, 95% CI: 1.12–2.88, P = 0.02). In RCTs, however, no significant difference was found between the two treatment strategies in the risk of all-cause mortality. CONCLUSIONS: The current meta-analysis showed that DEB and new-generation DES had comparable safety and efficacy for the treatment of ISR in RCTs. However, treatment with DEB was associated with higher risk of all-cause mortality in the real-world nonrandomized studies.